2017
DOI: 10.1021/acs.jafc.6b04509
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Key Aroma Compounds in Chinese Vidal Icewine by Gas Chromatography–Olfactometry, Quantitative Measurements, Aroma Recombination, and Omission Tests

Abstract: The key aroma compounds of Chinese Vidal icewine were characterized by means of gas chromatography-olfactometry (GC-O) coupled with mass spectrometry (MS) on polar and nonpolar columns, and their flavor dilution (FD) factors were determined by aroma extract dilution analysis (AEDA). A total of 59 odor-active aroma compounds in three ranks of Vidal icewines were identified, and 28 odorants (FD ≥ 9) were further quantitated for aroma reconstitution and omission tests. β-Damascenone showed the highest FD value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…Six terpenes were detected in all samples and three compounds with OAV above one, including linalool (sweet and floral note), geraniol (floral note), and cis -rose oxide (floral note). There were no significant differences in the contents of linalool (40.9–47.2 μg/L) and geraniol (1921.1–1936.4 μg/L) among all samples, while cis -rose oxide, generating lychee and rose smell to Vidal icewine (Ma et al, 2017 ), showed significant increment by mixed fermentation with 30.0% raise in SE-4- HV 11/ SC 45 wine relative to SC 45 wine ( p < 0.05), followed by SE-2- HV 11/ SC 45 wine and SI HV 11/ SC 45 wine. β-Damascenone and phenylacetaldehyde are the key odorants in Vidal icewine and impart floral and honey notes to icewine (Ma et al, 2017 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Six terpenes were detected in all samples and three compounds with OAV above one, including linalool (sweet and floral note), geraniol (floral note), and cis -rose oxide (floral note). There were no significant differences in the contents of linalool (40.9–47.2 μg/L) and geraniol (1921.1–1936.4 μg/L) among all samples, while cis -rose oxide, generating lychee and rose smell to Vidal icewine (Ma et al, 2017 ), showed significant increment by mixed fermentation with 30.0% raise in SE-4- HV 11/ SC 45 wine relative to SC 45 wine ( p < 0.05), followed by SE-2- HV 11/ SC 45 wine and SI HV 11/ SC 45 wine. β-Damascenone and phenylacetaldehyde are the key odorants in Vidal icewine and impart floral and honey notes to icewine (Ma et al, 2017 ).…”
Section: Resultsmentioning
confidence: 95%
“…There were no significant differences in the contents of linalool (40.9–47.2 μg/L) and geraniol (1921.1–1936.4 μg/L) among all samples, while cis -rose oxide, generating lychee and rose smell to Vidal icewine (Ma et al, 2017 ), showed significant increment by mixed fermentation with 30.0% raise in SE-4- HV 11/ SC 45 wine relative to SC 45 wine ( p < 0.05), followed by SE-2- HV 11/ SC 45 wine and SI HV 11/ SC 45 wine. β-Damascenone and phenylacetaldehyde are the key odorants in Vidal icewine and impart floral and honey notes to icewine (Ma et al, 2017 ). Due to low sensory threshold (0.05 and 1 μg/L, respectively), small variation of their concentrations can result in significant influence on the entire aroma profiles of wines.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The most odor‐potent compounds of Riesling and Vidal ice wines were β ‐damascenone, oct‐1‐en‐3‐ol, ethyl octanoate, cis ‐rose oxide, and ethyl hexanoate . Recently, the chemosensory characteristics were investigated as well as the key aroma compounds in Vidal ice wine …”
Section: Introductionmentioning
confidence: 99%
“…[12] Recently, the chemosensory characteristics were investigated [13] as well as the key aroma compounds in Vidal ice wine. [14] In contrast to standard wines, the composition of wines produced after late, and especially after ice harvest, has been studied much less. Particularly, on late and ice harvest Gew€ urztraminer wine there is only one article [15] reporting the changes in physico-chemical and volatile aroma compound composition (determined solely by HS-SPME-GC/MS).…”
Section: Introductionmentioning
confidence: 99%